Evaluation of Some Hematological Parameters in HCV Infected Patients Among Blood Donors at Thi-Qar Province: Evaluasi Beberapa Parameter Hematologi pada Pasien yang Terinfeksi HCV di Antara Donor Darah di Provinsi Thi-Qar - Ahmed Hieran Ramadhan Al-Jabery; Hayder Fadhil Okab; Ali Obeid Ibrahim Alkafaji; Ali Hussein Hammoud; Saif Al-Din Saad; Radha Mohammed Radhi; Abbas Mohammed Naji; Zain Al-Abidin Adel Al-Abadi; Mohammed Hassan Aneed (Academia Open, 2024)
Hepatitis C virus is a major health problem because of its effect on the liver and health and its being life-threatening if not treated early. It also affects the blood parameters of those infected. The current study conducted in Thi-Qar province revealed changes in some blood parameters of the infected group compared to the control group, where a slight decrease was recorded in WBCs, RBCs, PCV, MCV, MCH, PLT, Lymp. but no significant differences were found, except for red blood cells, which were 0.03 at a significant level 0.05. It was also found that the highest infection rate was in the age group of 30-39 years, while no infection was recorded in the age group of 50-59 years. Highlights: Hepatitis C impacts liver health and alters blood parameters. Significant RBC change noted; highest infection in 30–39 age group. No infections in the 50–59 age group recorded. Keywords: HCV, Hematological, ELISA, Thi-Qar